2021
DOI: 10.1016/j.cegh.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social factors associated with the nationwide lockdown in India during COVID- 19 pandemic

Abstract: To investigate the psycho-social factors associated with COVID-19 and the nationwide lockdown in India. Study design: An online survey was conducted from April 11 through April 16, 2020 in 28 states and 8 union territories (UT) of India. The potential participants were recruited using snowball sampling procedure. Methods: A cross-sectional online survey was conducted among the people of all states in India. A spatial analysis was performed and Moran's I statistic was applied to investigate the overall clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…Our results indicate that PwE in our sample complied well with national lockdown measures. According to our survey, only 2.8% of respondents stated that they never or rarely complied with the lockdown measures, which is very similar to the results of a research obtained in India that was performed on the general population [6] . A common characteristic among these respondents in our sample was that they did not feel anxiety about the COVID-19 pandemic, which was one of the risk factors of non-compliance with self-isolation measures in the UK [7] .…”
Section: Discussionsupporting
confidence: 87%
“…Our results indicate that PwE in our sample complied well with national lockdown measures. According to our survey, only 2.8% of respondents stated that they never or rarely complied with the lockdown measures, which is very similar to the results of a research obtained in India that was performed on the general population [6] . A common characteristic among these respondents in our sample was that they did not feel anxiety about the COVID-19 pandemic, which was one of the risk factors of non-compliance with self-isolation measures in the UK [7] .…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the findings of other authors. [ 22 ] In keeping with other studies our respondents with a self-reported mental illness reported worsened symptoms or living in fear of mental health relapse. [ 23 ] There is therefore a need for health care systems to invest in programmes to better support people with a pre-existing mental illness during a pandemic by understanding their coping strategies and reinforcing these to increase resilience so that they can be applied during a crisis situation such as a pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…Because of the population and population density lockdown was needed [ 102 ]. It should be mentioned that the People of India followed the Government prescribed rules and were knowledgeable about the drastic impact of COVID-19 hence tried to abide by the regulations [ 103 , 104 ]. Lockdown reduced the transmission and several countries got success from it.…”
Section: Discussionmentioning
confidence: 99%